Determination Effects of Active Dry Yeast on Morphological and Chemical Components of Maize Plants Grown in Alkaline Soils for Silage Purposes - Mohammad Gazy ALOBAIDY; Zübeyir AĞIRAĞAÇ; Şeyda ZORER ÇELEBİ (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
In agriculture, the use of environmentally friendly materials both in place of and alongside chemical ones is continuously increasing. Two field experiments were conducted during the 2019 and 2020 seasons to investigate the effects of foliar application of three doses (5.0, 7.5, and 10 g L-1) of active dry yeast were sprayed on maize (Zea mays L. Cv. Tuano) at two intervals, the first 54 days after planting (DAP), and the second 15 days later. Plants were grown for silage purposes under alkaline soil conditions at the Experimental and Research Station of the Field Crops Dep., Van Yuzuncu Yıl University-(VYYU), Turkey. Measurements were taken three times at the vegetative stage 64, 74, and 84-DAP, and one times at the dough stage 117-123 DAP. Morphologically, the results showed that the foliar application of different doses of yeast increased the plant height (cm), stem, leaves, and cobs weight per plant and total plant weight (g), number of cobs plant-1 (piece), and green and dry herbage yield (ton da-1) at 117-123 DAP during the two seasons. In contrast, there was no significant increase in plant height (cm), chlorophyll as SPAD (The Soil Plant Analysis Development) value, and the number of leaves per plant at 64 DAP. Chemically, the spraying of the yeast improved the P, K, Ca, Mg, Fe, Cu, Se, and Zn concentrations at 117-123 DAP as well as chlorophyll content at 74 and 84 DAP compared to the control. From this study, it could be concluded that the highest values of the studied parameters were recorded when active dry yeast was used at a dose of 10 g L-1 on maize under high pH soil.